Proceedings of XVth International Workshop on Polarized Sources, Targets, and Polarimetry — PoS(PSTP2013) 2014
DOI: 10.22323/1.182.0060
|View full text |Cite
|
Sign up to set email alerts
|

Two Novel Approaches for Electron Beam Polarization from Unstrained GaAs

Abstract: Two novel approaches to producing highly-polarized electron beams from unstrained GaAs were tested using a micro-Mott polarimeter. Based on a suggestion by Nakanishi [1]], twophoton photoemission with 1560 nm light was used with photocathodes of varying thickness: 625m, 0.32m, and 0.18m. For each of these photocathodes, the degree of spin polarization of the photoemitted beam was less than 50%. Polarization via two-photon absorption was highest from the thinnest photocathode sample and close to that obtaine… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 14 publications
0
1
0
Order By: Relevance
“…Usually the electron spin-polarization yield (ESP) is between 30–50%, depending on dopant concentration, temperature and the operation mode for unstrained bulk GaAs. 136,137 Demonstrations at SLAC showed that a polarization yield up to 80% was achieved with high-gradient doped strained GaAs. 138 However, the highest polarization yield of 84% at 6.4% QE was reported on superlattice structured GaAs with a distributed Bragg reflector (DBR).…”
Section: Semiconductor Photocathodesmentioning
confidence: 99%
“…Usually the electron spin-polarization yield (ESP) is between 30–50%, depending on dopant concentration, temperature and the operation mode for unstrained bulk GaAs. 136,137 Demonstrations at SLAC showed that a polarization yield up to 80% was achieved with high-gradient doped strained GaAs. 138 However, the highest polarization yield of 84% at 6.4% QE was reported on superlattice structured GaAs with a distributed Bragg reflector (DBR).…”
Section: Semiconductor Photocathodesmentioning
confidence: 99%